2022
DOI: 10.1101/2022.04.01.486690
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A co-operative knock-on mechanism underpins Ca2+-selective cation permeation in TRPV channels

Abstract: The selective exchange of ions across cellular membranes is a vital biological process. Ca2+-mediated signalling is implicated in a broad array of physiological processes in cells, whilst elevated intracellular concentrations of Ca2+ are cytotoxic. Due to the significance of this cation, strict Ca2+ concentration gradients are maintained across the plasma and organelle membranes. Therefore, Ca2+ signalling relies on permeation through selective ion channels that control the flux of Ca2+ ions. A key family of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 85 publications
2
16
0
Order By: Relevance
“…Therefore, multiple Ca 2+ ions must line up and march in a concerted manner to permeate more efficiently. Consequently, multiple Ca 2+ binding sites lead to a concerted permeation manner, which is a characteristic that discriminates the Ca 2+ permeation in TRPV6 from TRPV1, as also observed by Ives et al (Ives et al, 2022). In fact, increasing the number of Ca 2+ -binding sites in channel pores has long been proposed to improve channel selectivity for Ca 2+ (Tsien et al, 1987).…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Therefore, multiple Ca 2+ ions must line up and march in a concerted manner to permeate more efficiently. Consequently, multiple Ca 2+ binding sites lead to a concerted permeation manner, which is a characteristic that discriminates the Ca 2+ permeation in TRPV6 from TRPV1, as also observed by Ives et al (Ives et al, 2022). In fact, increasing the number of Ca 2+ -binding sites in channel pores has long been proposed to improve channel selectivity for Ca 2+ (Tsien et al, 1987).…”
Section: Discussionsupporting
confidence: 63%
“…Thus, monovalent cations can probably still push Ca 2+ through SF, resulting in a lower valence selectivity than expected. Indeed, Ives et al’s work observed similar behavior for multiple TRPV channels, as well as that the selectivity increases in TRPV5 with decreasing the transmembrane potential (Ives et al, 2022).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In the case of simulations containing Ca 2+ , the standard CHARMM36m Ca 2+ ions were then replaced with the multi-site Ca 2+ of Zhang et al Zhang et al ( 2020 ). This multi-site model has used been used to investigate Ca 2+ permeation in a number of channels, including including the type-1 ryanodine receptor Zhang et al ( 2020 ); Liu et al ( 2021 ), AMPA receptors Schackert et al ( 2022 ), the E protein of SARS-CoV-2 Antonides et al ( 2022 ), and TRPV channels Ives et al ( 2022 ); Liu and Song ( 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…To characterise the level of co-operativity in the knock-on permeation mechanisms of the TRPM5 channel, we used PENSA to calculate the state-specific information (SSI) shared between discrete state transitions in the occupancy distributions of both of the binding sites Thomson et al ( 2021 ); Vögele et al ( 2022 ). The methodology used is the same as that described in detail in our previous work Ives et al ( 2022 ).…”
Section: Methodsmentioning
confidence: 99%